Todays Need in Pediatric Practice: Quadrivalent Inactivated Influenza Vaccine-Split Virion - Kailas Patil, Amol (International Journal of Recent Advances in Multidisciplinary Topics, 2021)
Vaccination is the backbone in children’s growth year. All types of vaccine should be necessary in pediatric age group. Since last year our country suffering from covid 19 pandemic. As per govt prediction next third wave will be on pediatric age group. So we have to prepare for it, as a part of preparation govt asked to give Influenza vaccine to pediatric age group but there is n number of vaccine available in market. My current article is about quadrivalent inactivated influenza vaccine. Description: Quadrivalent Influenza Vaccine for intramuscular injection is an inactivated influenza vaccine, prepared from influenza viruses propagated in embryonated chicken eggs Ingredients: A (H1N1), A (H3N2), B/(Victoria lineage), B/(Yamagata lineage) Indications and usage: Above 6 months to 65years Dosage and administration: 0.25ml/0.5ml (1 or 2 doses 4 weeks apart) Contraindications: A severe allergic reaction (e.g., anaphylaxis) to any component of the vaccine. Including egg protein, or to a previous dose of any influenza vaccine is a contraindication to administration. A severe allergic reaction (e.g. anaphylaxis) to any component of the vaccine. Including egg protein, or to a previous dose of any influenza vaccine is a contraindication to administration. Use in specific populations: This vaccine should be given to a pregnant woman only if clearly needed. It is not known whether this vaccine is excreted in human milk. Safety and effectiveness of this vaccine in children below the age of 6 months have not been established. Antibody responses to this vaccine are lower in persons more than 65 years of age than in younger adults.